The independent and interdependent self-affirmations in action: Understanding their dynamics in India during the early phase of the COVID-19 lockdown - Tiwari, Gyanesh Kumar; Shukla, Anurag; Macorya, Amit Kumar; Singh, Archana; Choudhary, Archna (Journal of Psychological Perspective, 2024)
The study explored the role of two dissimilar familial and religious practices in distinctly shaping independent and interdependent self-affirmations in two value systems (individualism and collectivism) that emerged to protect self-integrity and self-worth challenged by the threats of COVID-19. A qualitative research design was employed. A heterogeneous sample of 19 participants (10 joint and 9 nuclear families) was recruited who reported in a semi-structured interview about the consequences of COVID-19 and the role of family and religious values in coping with the pandemic threats. The thematic method was used to analyse the data. Codes were generated using a priori criteria while reviewing and re-reviewing, multiple discussions and iterations helped in theme identification and ascertaining validity. Five themes were generated: perceived strong threat of COVID-19, dissimilar genesis of independent and interdependent self-affirmations, positive roles of joint familial values, significance of religious values, and traditional and modern religious routes of self-affirmation. Threats were expressed in experiences of anxiety, uncertainty and mood fluctuations. Interdependence, affiliation and support were joint familial values whereas independence and self-esteem reflected nuclear family-values. Focus on explicit attributes denoted modern while divine interpretation and will of God reflected traditional religious values. Novelty, uncertainty and incurability of COVID-19 caused threats to self-integrity that compelled hem to affirm their most preferred values originating from two family forms. The pandemic posed threats to their self-worth, which in turn, activated affirmations in two distinct value systems leading to the development of independent and interdependent self-affirmations. Study findings will help surface novel features of the two self-affirmations. It provides new insights for making successful behavioural changes at individual, group and community levels for the success of social, health and educational policies.